2020
DOI: 10.1128/jvi.01575-20
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin Signaling Activation Antagonizes Autophagy To Facilitate Zika Virus Replication

Abstract: Zika virus (ZIKV), a mosquito-transmitted flavivirus, is linked to microcephaly and other neurological defects in neonates and Guillain–Barré syndrome in adults. The molecular mechanisms regulating ZIKV infection and pathogenic outcomes are incompletely understood. Signaling by the mechanistic (mammalian) target of rapamycin (mTOR) kinase is important for cell survival and proliferation, and viruses are known to hijack this pathway for their replication. Here, we show that in human neuronal precursors and glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 87 publications
3
31
1
Order By: Relevance
“…The mammalian target of rapamycin (mTOR) is aberrantly phosphorylated and activated by PI3K-AKT signaling in many human malignancies, including HCC, and plays a critical role in HCC oncogenesis [19,33,34]. mTOR is a serine/threonine protein kinase and exist as two distinct forms: mTORC1 and mTORC2 [35,36]. Rapamycin-sensitive mTORC1 promote HCC growth and progression via directly targeting phosphorylation and activation of ribosomal protein S6 kinase (p70S6K) and eukaryotic translation initiation factor 4E-binding protein 1 (eIF4EBP1) [37].…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) is aberrantly phosphorylated and activated by PI3K-AKT signaling in many human malignancies, including HCC, and plays a critical role in HCC oncogenesis [19,33,34]. mTOR is a serine/threonine protein kinase and exist as two distinct forms: mTORC1 and mTORC2 [35,36]. Rapamycin-sensitive mTORC1 promote HCC growth and progression via directly targeting phosphorylation and activation of ribosomal protein S6 kinase (p70S6K) and eukaryotic translation initiation factor 4E-binding protein 1 (eIF4EBP1) [37].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this mechanism also plays an essential role in the degradation of labeled intracellular pathogens and in the induction of the antiviral response (Lee and Iwasaki, 2008;Deretic et al, 2013). Even though autophagy restricts WNV replication (Shoji-Kawata et al, 2013;Kobayashi et al, 2014), viruses such as DENV and ZIKV have successfully subverted this process to enhance their replication Chu et al, 2014;Liang et al, 2016;Sahoo et al, 2020).…”
Section: Autophagymentioning
confidence: 99%
“…Interestingly, ZIKV-induced autophagy activation has been associated with the early stages of infection. Sahoo et al (2020) reported that ZIKV induces autophagy early and transiently, and subsequently, the virus can reverse this activation to allow viral protein accumulation and virus replication in neuronal and glial cells; therefore, suppression of autophagy at late times of ZIKV infection is suggested necessary for its replication (Sahoo et al, 2020). Similarly, Metz et al (2015) reported a biphasic autophagy response to DENV infection, in which DENV infection initially activates it and then, later on, inhibits autophagy (Metz et al, 2015, p. 62).…”
Section: Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…In neuronal cells, Zika virus (ZIKV) infection activates mTORC2 through unknown mechanisms. The activation of mTORC2 facilitates ZIKV replication by negatively regulating autophagy (Sahoo et al, 2020). Upon influenza virus infection, the viral protein NS1 promotes mTORC2-mediated Akt-S473 phosphorylation, which inhibits cell apoptosis (Kuss-Duerkop et al, 2017).…”
Section: Regulation Through Virusmentioning
confidence: 99%